Penerapan Metode SWARA–COPRAS untuk Rekomendasi Pemilihan Jurusan Mahasiswa Baru di Universitas Semarang - Sri Ayu Panannangan; Saifur Rohman Cholil (Infotek: Jurnal Informatika dan Teknologi, 2026)
Choosing a college major is an important decision for prospective students as it affects academic performance and future career planning. However, in practice, many prospective students still experience difficulties in selecting a major that matches their interests, abilities, and preferences. Therefore, this study aims to apply the Simple Weighting Assessment Ratio Analysis (SWARA) and Complex Proportional Assessment (COPRAS) methods in developing a decision support system for college major selection. The SWARA method is used to determine criterion weights based on their level of importance, while the COPRAS method is applied to calculate utility values and rank alternative majors. The criteria used include academic ability, interests and experience, profile suitability, cost, and accreditation, with alternative majors consisting of Informatics Engineering, Information Systems, Civil Engineering, and Electrical Engineering. Data were collected from several respondents and processed according to the stages of the applied methods. The results show that each respondent receives different major recommendations based on the COPRAS ranking results. For respondent 1, alternatives A1 and A2 ranked first with a utility value of 100%, while other respondents obtained different top alternatives according to their respective preferences. Validation using Spearman’s Rank Correlation indicates strong to very strong relationships between system recommendations and respondents’ preferences, with one example correlation coefficient of 0.95. Based on these results, the developed decision support system is expected to assist prospective students in selecting college majors in a more structured and objective manner.